Theoretical perspectives in tourism dynamics - Oprescu, Georgiana (Technium Social Sciences Journal, 2023)
The definitions, classifications, dynamics, sociological significance of tourism along with its historical coordinates represent an introduction to this cultural, economic, social and political sphere, which has resisted, reinvented itself and been reborn like the Phoenix Bird over time, leaving its mark for entire generations and being the economic, social, cultural and even religious basis for different social identities. Sociology of Tourism helps us to analyze the impact of an individual passing through a system as well as a large number of tourists, to establish the transformative impact of tourism on people, places and communities and their way of life, planning and sustainable development.